HUBUNGAN ANTARA PEMANFAATAN LAYANAN BIMBINGAN KELOMPOK TERHADAP PENERIMAAN DIRI SISWA DI SMA MUHAMMADIYAH 1 SUMENEP - Alamsyah, Diky; Rusmiyati; Tri Yuliana, Anis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACK This study was motivated by the low level of self-acceptance among students at SMA Muhammadiyah 1 Sumenep, as reflected in their lack of self-confidence, difficulty accepting criticism, reluctance to express opinions, and challenges in accepting personal shortcomings. The research aimed to examine the relationship between the implementation of group guidance services and students’ self-acceptance.The study employed a quantitative approach using a correlational research design. The population consisted of 30 eleventh-grade students, while 20 students were selected as the sample through random sampling techniques. Data were collected using questionnaires that had previously undergone validity and reliability testing. The reliability test results showed Cronbach’s Alpha values of 0.636 for the group guidance variable and 0.638 for the self-acceptance variable, indicating that both instruments were sufficiently reliable for research purposes.Data analysis was conducted using the Pearson Product Moment correlation technique with the assistance of IBM SPSS Statistics 25. The findings revealed a positive and significant relationship between group guidance services and students’ self-acceptance. This was demonstrated by a correlation coefficient value of 0.828 with a significance level of 0.000 < 0.05. The correlation falls into the “very strong” category, indicating that better implementation of group guidance services is associated with higher levels of student self-acceptance.These findings suggest that group guidance services play an important role in supporting students’ personal and social development, particularly in fostering self-acceptance.